ANALISIS PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA SEBELUM DAN SESUDAH ADOPSI IFRS - Simangunsong, Andrian Hardianto; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of board of commissioners, audit committee, and audit quality on earning management before and after adoption of IFRS and this study also examine the difference between effect of board of commissioners, audit committee and audit quality on earning management before and after adoption of IFRS in Indonesia.This research was conducted by quantitative method and used data of non financial company listed in Indonesia Stock Exchange (IDX). The data was analyzed separately between two period by using multiple linear regression model. Total sample was 300 companies for each period. This research also used Chow test and Robustness test as an additional test.The result of this study showed that on before adoption of IFRS period, only audit quality has significant and positive effect on earning management. However on after adoption of IFRS period, this study showed that board of commissioners and audit committee have significant and positive effect on earning management. The result of chow test showed that there was structural change on effect of board of commissioners, audit committee and audit quality on earning management. The other test which is robusness test suggested that the interaction effect of audit quality and IFRS has significant and negative effect on earning management.